Sustainable supply chain managment and corporate performance in small and medium-scale construction enterprises - Mafundu, Robert Hamudiwamwe (Vaal University of Technology, 2022)
The contributions of the construction industry to South Africa’s economic development are widely acknowledged. Small to medium enterprises (SMEs) have become increasingly important players in the country's construction industry. The construction industry faces numerous challenges that are also well-known, and its SMEs remain severely exposed to these problems. This study investigated the relationship between sustainable supply chain management (SSCM) practices, supply chain sustainability, supply chain responsiveness and corporate performance in construction SMEs in South Africa. The study applied a quantitative approach using a structured survey questionnaire to collect data from 413 purposively selected SME owners, managers and professional employees drawn from construction SMEs in four provinces: Gauteng, Limpopo, Mpumalanga and North-West. The collected data was analysed using the Statistical Packages for Social Sciences (SPSS version 27.0 and the SMART Partial Least Squares (PLS) 3.0 statistical software. The actual data analysis techniques utilised comprised descriptive and inferential statistics and hypotheses were tested using structural equation modelling. The study results revealed that two SSCM practices, supply chain learning and supply chain responsibility, contributed positively to supply chain sustainability, which, in turn, predicted supply chain responsiveness. Moreover, supply chain responsiveness contributed positively to five corporate performance indicators, namely operational performance, operational agility, market performance, return on investment and profitability. The study underscores the importance of supply chain learning and responsibility as predictive drivers of sustainability and how the latter is an antecedent of the responsiveness of construction SME supply chains. These constructs were proven to be critical for the improvement of corporate performance. The study introduces a model demonstrating the interaction of these factors in the construction industry. This model may be adopted to improve supply chain sustainability, responsiveness and corporate performance in construction SMEs.
Ph. D. (Department of logistics and supply chain management: Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Supply chain management; Sustainable supply chain management; Supply chain responsiveness; Corporate performance; Small and medium construction companies; Dissertation, Academic -- South Africa.; Business logistics.; Small business.; Sustainability.